A numerical modelling and simulation of core-scale sandstone acidizing process: a study on the effect of temperature - Leong, V.; Ben Mahmud, Hisham; Law, M.; Foo, C.; Tan, I. (SpringerOpen, 2018)
A wide and comprehensive understanding of the chemical reactions and mechanisms of HBF4 is crucial as it significantly influences its performance in stimulating a sandstone formation. In general, it is well-known that HBF4 is able to provide a deeper penetration into the sandstone matrix before being spent due to its uniquely slow hydrolysis ability to produce HF. In the present study, a 3D numerical modelling and simulation were conducted to examine the capability of HBF4 in enhancing the porosity and permeability of the sandstone matrix. The model is built in COMSOL® Multiphysics commercial software of computational fluid dynamics (CFD) to simulate the acid core flooding process on sandstone core. The model had been validated against the experimental data in the literature. The results matched with the measured plot data very well. The effect of temperature on the performance HBF4 sandstone acidizing is evaluated in this study. The simulation results indicated that at low temperature of 25 °C, HBF4 is not very effective, as justified in its poor porosity and permeability increments of only 1.07 and 1.23, respectively. However, at elevated temperatures, the porosity and permeability enhancement also become increasingly more significant, which showed 1.26 and 2.06, respectively, at 65 °C; and 1.67 and 7.06, respectively, at 105 °C. Therefore, one can conclude that HBF4 acid treatment performed better at elevated temperatures due to increased hydrolysis rate, which is a governing function in HBF4 sandstone acidizing. Overall, this model had provided a reliable alternative to optimize various other parameters of HBF4 acid treatment.